Comparison between intrathecal bupivacaine and combination of bupivacaine and midazolam for postoperative pain relief after infraumbilical elective surgeries - Sharma, Neha; Shukla, Chetan (International Journal of Research in Medical Sciences, 2020)
Background: Objective of the study was to identify the efficacy of midazolam as an adjuvant to intrathecal hyperbaric bupivacaine 0.5%, a prospective, randomized, double blind study was conducted to compare the onset, duration of sensory and motor block, postoperative analgesia, hemodynamic changes and complications. Methods: Sixty patients, ASA I/II, Age 18-60 year, scheduled for infraumbilical surgeries, were randomly allocated to group BNS(n=30) to receive intrathecally 2.5 ml of 0.5% hyperbaric bupivacaine with 0.4 ml normal saline; and group BM (n=30) to receive 2.5 ml of 0.5% hyperbaric bupivacaine +2 mg preservative free midazolam 0.4 ml (5mg/ml). We observed onset, duration and regression of sensory and motor block, degree of sedation and pain scores, hemodynamic changes and adverse effects. (PS) version 3.0.0.34 was used for power and sample size calculation. Statistical analysis was performed using Microsoft (MS) office excel software with the student’s t-test and chi-square test (P=0.05) Results: Highest level of sensory blockade (p<.05), motor block duration (179.67±14.94 vs 151.83±10.96 min), sensory block duration (222±16.5 vs 174±12.53 min) and time to first requirement of i.v. analgesia were significantly higher in group BM. Postoperative VAS score was significantly less in group BM. Both groups were comparable in demographic data and hemodynamic changes. Conclusions: Intrathecal 2 mg midazolam found as an attractive adjuvant to 0.5% hyperbaric bupivacaine in spinal anesthesia in infraumbilical surgeries by producing significantly longer duration of motor and sensory block, good quality of intraoperative and postoperative analgesia with less incidence of nausea vomiting as compared to bupivacaine alone.